Analisis Semiotika Makna Pesan Persahabatan Dalam Film Belok Kanan Barcelona (2018) - Kristina, Marya; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2024)
A film is a form of visual art that utilizes moving images and sound to convey a story or message. The film "Belok Kanan Barcelona" (2018) focuses on the theme of friendship within the context of a journey undertaken by a group of students in Barcelona. This study aims to describe the results of the analysis of signifiers and signifieds and to reveal the meaning of the message of friendship through a descriptive qualitative approach, using Ferdinand De Saussure's theory. The data collection methods employed include observation, documentation, and literature study, with the object of research being the film "Belok Kanan Barcelona." The results of the study indicate that there are four main components of friendship in the film, namely trust and support, openness and presence, loyalty and sacrifice, and acceptance and understanding.